Mechanisms of follicular atresia: focus on apoptosis, autophagy, and ferroptosis - Zhang, Tongqing; Lin, Menghan; Wang, Chuangui; Zhou, Jiaqi (Frontiers in Endocrinology, 2025)
Follicular atresia is a critical physiological process that ensures the selection of high-quality oocytes by eliminating non-viable follicles. In women, 99.9% of follicles undergo atresia naturally, the premature or dysregulated atresia follicle can lead to pathological conditions such as polycystic ovary syndrome (PCOS) and premature ovarian failure (POF). Recent studies highlight the roles of apoptosis, autophagy, and ferroptosis in regulating follicular atresia. This review integrates molecular mechanisms of programmed cell death with follicular dynamics, emphasizing how aberrant atresia disrupts reproductive health. We discuss therapeutic strategies targeting these pathways to mitigate pathological atresia, offering insights into preserving ovarian reserve and improving fertility outcomes.